How does Religiosity and Tourist's Perception Play a Role to Attract Visiting Halal Tourism Destination? - Fathurrohman Husen; Nurkholish Majid (Journal of Islamic Studies and Education, 2023)
This study aims to look at the influence of religiosity and tourists' perceptions of halal tourism on their intention to visit halal tourist destinations. With the quantitative method, the research respondents were 100 tourists who had visited halal tourist destinations. Data was collected through a questionnaire and then processed using the Partial Least Square method to analyze the validity of the data and test the hypothesis. The results of the study show that perceptions of halal tourism are able to attract visits to halal tourist destinations. However, religiosity (moderating variable) is not able to attract interest in visiting and is unable to moderate the increase in visitor perceptions of halal tourist destinations.